A STUDY OF THE IMPACT OF IMPLEMENTING AN INNOVATIVE APPROACH-BASED VEGETABLE CULTIVATION PROGRAMME WITH THE USE OF IOT-BASED SMART FARMING TECHNOLOGY ON INCREASING THE WORK PRODUCTIVITY OF FARM WOMEN GROUP MEMBERS - Susridar, Susridar; Khasanah, Nur; Pangestu, Gayatri (Institute of Computer Science (IOCS), 2025)
Farmer groups often face various obstacles in the production process, one of which is low labour productivity. This low productivity can lead to a waste of resources, which in turn has an impact on reducing profits. In response to these problems, PIKMa Universitas Putra Bangsa initiated a program entitled Innovative Approaches to Vegetable Cultivation with the Utilisation of IoT-Based Smart Farming Technology aimed at the Women Farmers Group in Jatimulyo Village. This programme was submitted as part of the PPK ORMAWA activity funded by DIKTI. In order for the implementation of the programme to run optimally and the use of government funds not to be wasted, a comprehensive evaluation of the impact of the programme is needed. This study aims to assess the effect of an innovative vegetable cultivation programme based on smart farming technology on increasing the work productivity of the Women Farmers Group in Jatimulyo Village, Alian District. All members of the women's farmer group in the village were sampled. Primary data were collected and analysed using the simple linear regression method, after first conducting validity and reliability testing. The results showed that the IoT-based smart farming programme had a significant effect on increasing labour productivity in the target group.